Causes and Consequences of Sports Concussion. Issue 2 (June 2014) - Edwards, Jonathan C.; Bodle, Jeffrey D.
<x xml:space="preserve">Abstract</x> Concussion in sports is a topic that is receiving increasing amounts of publicity and attention. Increasing recognition of concussion as well as improving understanding of the short‐ and long‐term physiologic effects of concussion have resulted in widespread legislation governing the recognition and treatment of sports concussion. The increasing amount of medical research in the field and oftentimes subjective symptoms of concussion leave many ethical questions to be answered.